Eco-morphological diversity of fish fauna in a tropical man-made lake, Southwestern Nigeria - Kazeem, Kazeem O.; Olanrewaju, Nurudeen A. (Syiah Kuala University, 2025)
Eco-morphological studies seek to understand the interconnection between the morphology of an organism and its ecology. It is the only way to determine if morphometric data can be used as an informative proxy for ecological variables of interest. This study, therefore, investigated fish diversity and its eco-morphological features for sustainable fish production in the Oyan Dam. The ichthyofauna of the Oyan Dam was surveyed from November 2021 to April 2022, and data on the abundance, diversity, and ecomorphological traits were obtained following standard procedures. Data collected were analyzed using descriptive statistics, Bootstrap resampling, and Multivariate statistics. A total of 466 piscine specimens were sampled which belonged to seven orders, 13 families, and 26 species. Four families including Cichlidae, Mormyridae, Schilbeidae, and Ariidae were dominant and constituted 66.74% of the total catches. Margalef (3.50.02) and dominance (0.470.01) index values suggest that Oyan Dam is highly diverse with abundant fish species. The assemblage of fish species in Oyan Dam is ecomorphologically structured. However, the main ecomorphological traits verified in this study were compression index (CI), aspect of pectoral fin ratio (APFR), and caudal peduncle compression index (CPCI). These ecomorphological attributes indicated the relationship between the morphology of the species and their potential niches.